Framework Sustainability Strategy, Inhotim, Brazil (Cadernos de Sociomuseologia, 2019)
The presentation discusses possibilities of strategic action to the Inhotim Museum, located in the state of Minas Gerais, in Brazil, focusing in a sustainable process to further develop the institution. Those proposals are constructed from three broad concepts: the museum, sustainability and strategy, with the balance between those three dimensions as the key for all the process. Keywords: Inhotim Museum, sustainability, strategy